International Experience of Legal Support of Information Security and the Possibilities for its Application in the Republic of Kazakhstan - Sholpan, Zabikh (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2020)
The author in the article considers the problems of ensuring information security for the solution of which it is supposed to study methods and ways for identifying and preventing danger in the information sphere. The information security of society as a whole is determined by the rapidly growing technological capabilities of modern information systems, which in their influence on the politics, economy, and the spiritual and ideological sphere of people have now become decisive. Ensuring information security, which refers to the state of protection of the vital interests of the individual, society and the state in the information sphere from internal and external threats, seems to be a very important task in the modern world. The security of the information space are entails the protection of the rights and interests of man and citizen, society and the state in the information sphere from real and potential threats. The article also provides a generalized description of the international experience in the legal regulation of information security and the possibility of its application in the Republic of Kazakhstan.

W artykule autor rozważa problemy zapewnienia bezpieczeństwa informacji, dla których rozwiązania ma zbadać metody i sposoby identyfikacji oraz zapobiegania zagrożeniom w sferze informacyjnej. O bezpieczeństwie informacyjnym społeczeństwa jako całości decydują szybko rosnące możliwości technologiczne nowoczesnych systemów informacyjnych, które w swoim wpływie na politykę, gospodarkę oraz sferę duchową i ideologiczną ludzi stały się obecnie decydujące. Zapewnienie bezpieczeństwa informacji, które dotyczy stanu ochrony żywotnych interesów jednostki, społeczeństwa i państwa w sferze informacyjnej przed zagrożeniami wewnętrznymi i zewnętrznymi, wydaje się być bardzo ważnym zadaniem we współczesnym świecie. Bezpieczeństwo przestrzeni informacyjnej wiąże się z ochroną praw i interesów człowieka i obywatela, społeczeństwa i państwa w sferze informacyjnej przed rzeczywistymi i potencjalnymi zagrożeniami. W artykule przedstawiono również uogólniony opis międzynarodowych doświadczeń w zakresie regulacji prawnej bezpieczeństwa informacji oraz możliwości ich zastosowania w Republice Kazachstanu.
Międzynarodowe doświadczenie w zakresie prawnego wsparcia bezpieczeństwa informacji i możliwości ich zastosowania w Republice Kazachstanu
Keywords: information security; information technology; media; Internet; laws; international law; bezpieczeństwo informacji; technologie informacyjne; media; internet; prawo; prawo międzynarodowe Article submitted: